Điều khiển bền vững hệ mimo với bất định đầu vào - Phàn, Vũ Ngọc (Journal of Computer Science and Cybernetics, 2016)
In the present paper we examine the problem of robust control where the reference input to be tracked by the plant output contains uncertainties. In the first section the internal model principle will be described for showing in what way the following of reference input can be realized. The specification of reference input will be explained in section 2 where the two sets of normalized signals are introduced. In the next section, section 3, the fundamentals of the optimal control in the frequency domain will be presented and discussed. Finally, in section 4 a design roach will be provided to solve the tracking problem under the circumstance of reference input uncertainty.